2004
DOI: 10.1161/01.cir.0000109494.05317.58
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone Therapy for Drug-Refractory Fetal Tachycardia

Abstract: Background-Fetal tachycardia complicated by ventricular dysfunction and hydrops fetalis carries a significant risk of morbidity and mortality. Transplacental digoxin is effective therapy in a small percentage, but there is no consensus with regard to antiarrhythmic treatment if digoxin fails. This study evaluates the safety, efficacy, and outcome of amiodarone therapy for digoxin-refractory fetal tachycardia with heart failure. Methods and Results-Fetuses with incessant tachycardia and either hydrops fetalis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(70 citation statements)
references
References 37 publications
0
69
0
1
Order By: Relevance
“…16) Some studies have successfully detected lethal cardiac arrhythmias with fetal MCGs. 17,18) However, while highly sensitive, such devices are large and unsuitable for ICU and emergency room bedside recordings.…”
Section: Fetal Ecg Recordingmentioning
confidence: 99%
“…16) Some studies have successfully detected lethal cardiac arrhythmias with fetal MCGs. 17,18) However, while highly sensitive, such devices are large and unsuitable for ICU and emergency room bedside recordings.…”
Section: Fetal Ecg Recordingmentioning
confidence: 99%
“…Digoxin has been widely accepted as the mainstay of therapy because of its safety and convenient administration 1,2,5 . Flecainide, sotalol and amiodarone has also been used in the treatment of fetal tachyarrhythmias 5,9,10 . However, more serious side effects on both mother and fetus have been a concern 5 .…”
Section: Discussionmentioning
confidence: 99%
“…9 Another study on refractory cases of foetal tachycardia reported a success rate of 93% in the treatment of foetal SVT in hydropic foetuses using amiodarone. 10 We used amiodarone as a drug for the first-line of treatment of our patient since hydrops had already developed.…”
Section: Discussionmentioning
confidence: 99%